2015
DOI: 10.3389/fpsyg.2015.00713
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of different displays in enhancing illusions of self-movement (vection)

Abstract: Illusions of self-movement (vection) can be used in virtual reality (VR) and other applications to give users the embodied sensation that they are moving when physical movement is unfeasible or too costly. Whereas a large body of vection literature studied how various parameters of the presented visual stimulus affect vection, little is known how different display types might affect vection. As a step toward addressing this gap, we conducted three experiments to compare vection and usability parameters between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 47 publications
0
25
0
2
Order By: Relevance
“…That is, the two displays with the largest FOV—StreetLab and the combination of three screens—resulted in strongest vection ratings overall. Previous research found similar results, showing that a smaller FOV typically reduces the sensation of vection (e.g., Allison et al., 1999; Dichgans & Brandt, 1978; Flanagan et al., 2002; Riecke & Jordan, 2015). The role of visual stimulation of the peripheral and central FOV has been exhaustively discussed in this context (e.g., Berthoz, Pavard, & Young, 1975; Warren & Kurtz, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…That is, the two displays with the largest FOV—StreetLab and the combination of three screens—resulted in strongest vection ratings overall. Previous research found similar results, showing that a smaller FOV typically reduces the sensation of vection (e.g., Allison et al., 1999; Dichgans & Brandt, 1978; Flanagan et al., 2002; Riecke & Jordan, 2015). The role of visual stimulation of the peripheral and central FOV has been exhaustively discussed in this context (e.g., Berthoz, Pavard, & Young, 1975; Warren & Kurtz, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…They reported persistence of vection in the same direction as the adapted one. The problem with subjective reports is that they do not allow quantification of the aftereffect magnitude and may be vulnerable to biases induced by experimental instructions (for a recent comparsion of vection onset latency and strength for 3D and head-mounted displays see Riecke and Jordan, 2015). These findings are highly suggestive but they provide only a subjective measure of aftereffect strength.…”
Section: Visuo-vestibular Crossmodal Aftereffects In Self-motion Percmentioning
confidence: 99%
“…and indirectly by altering the visual scene. For example, in recent research (simulating active pursuit of a target over a ground plane) Riecke and Jordan (2015) found that most subjects reported vection was greater through an HMD than on a 3D tv [37]. Interestingly, the HMD did not appear to be more provocative in terms of generating motion sickness.…”
Section: Relationship Between Vection and Cybersickness In Hmdsmentioning
confidence: 99%
“…Early findings (using fixed-based simulators rather than HMDs) suggested that traditional vection might be a prerequisite for visually induced motion sickness in stationary observers [25]. However, while fixed-base simulator studies have often reported positive correlations between vection and visually induced motion sickness [14,[31][32][33], other studies appeared to suggest negative relationships between the two phenomena [34], and still others failed to find significant relationships between them [4,28,[35][36][37].…”
Section: Relationship Between Vection and Cybersickness In Hmdsmentioning
confidence: 99%
See 1 more Smart Citation